Tectonic significance of Cenozoic exhumation and foreland basin evolution in the Western Alps. Issue 8 (19th August 2016) - Carrapa, Barbara; Di Giulio, Andrea; Mancin, Nicoletta; Stockli, Daniel; Fantoni, Roberto; Hughes, Amanda; Gupta, Sanjeev
Abstract: The Alps are the archetypical collisional orogenic system on Earth, and yet our understanding of processes controlling topographic growth in the Cenozoic remains incomplete. Whereas ideas and models on the Alps are abundant, data from the foreland basin record able to constrain the timing of erosion and sedimentation, mechanisms of basin accommodation and basin deformation are sparse. We combine seismic stratigraphy, micropaleontology, white mica 40 Ar/ 39 Ar, detrital zircon (U‐Th)/He and apatite fission track thermochronology to Oligocene‐Pliocene samples from the retrowedge foreland basin (Saluzzo Basin in Italy) and to Oligocene‐Miocene sedimentary rocks from the prowedge foreland basin (Bârreme Basin in France) of the Western Alps. Our new data show that exhumation in the Oligocene‐Miocene was nonuniform across the Western Alps. Topographic growth was underway since the Oligocene and exhumation was concentrated on the proside of the orogenic system. Rapid and episodic early Miocene exhumation of the Western Alps was concentrated instead on the retroside of the orogen and correlates with a major unconformity in the proximal retroforeland basin. A phase of orogenic construction is recorded by exhumation of the proximal proforeland in both the Central and Western Alps at circa 16 Ma. This is associated with high sedimentation rates, and by inference erosion rates, and suggests that an increase in accretionary flux associated with the dynamics of subduction of Europe under Adria controlled orogenic expansion in the Miocene. Key Points: Topographic growth in the Alps is the result of asymmetric and episodic Oligo‐Miocene exhumation Miocene exhumation and retroforeland deformation indicate a phase of orogenic construction Miocene orogenic growth is controlled by an increase in accretionary flux